2015
DOI: 10.1038/ncomms8659
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole is an antituberculous prodrug targeting cytochrome bc1

Abstract: Better antibiotics capable of killing multi-drug-resistant Mycobacterium tuberculosis are urgently needed. Despite extensive drug discovery efforts, only a few promising candidates are on the horizon and alternative screening protocols are required. Here, by testing a panel of FDA-approved drugs in a host cell-based assay, we show that the blockbuster drug lansoprazole (Prevacid), a gastric proton-pump inhibitor, has intracellular activity against M. tuberculosis. Ex vivo pharmacokinetics and target identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(191 citation statements)
references
References 23 publications
5
183
0
3
Order By: Relevance
“…As an example, with M. tuberculosis, it has recently been shown that the heartburn/proton pump inhibitor drug lansoprazole is metabolized to lansoprazole sulfide (structures in Fig. 6), which has potent activity against M. tuberculosis inside macrophages (85), and similar antibacterial effects are seen with omeprazole (which is reduced to the active sulfide) in Helicobacter pylori (86), as well as with rabeprazole (87,88). Lansoprazole, omeprazole, and rabeprazole are all proton pump inhibitors that contain benzimidazole groups with sulfoxide substituents.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, with M. tuberculosis, it has recently been shown that the heartburn/proton pump inhibitor drug lansoprazole is metabolized to lansoprazole sulfide (structures in Fig. 6), which has potent activity against M. tuberculosis inside macrophages (85), and similar antibacterial effects are seen with omeprazole (which is reduced to the active sulfide) in Helicobacter pylori (86), as well as with rabeprazole (87,88). Lansoprazole, omeprazole, and rabeprazole are all proton pump inhibitors that contain benzimidazole groups with sulfoxide substituents.…”
Section: Resultsmentioning
confidence: 99%
“…Some drugs identified in in vitro screens have previously been shown to have some antimicrobial activity, such as TFP and proton pump inhibitors, such as pantoprazole, which are known antituberculars (52,53). After validating that none of the 58 drugs from the more clinically relevant posttreatment Growth was continued at 28°C for 2 h, followed by a temperature shift to 37°C for an additional 3 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of point mutations in M. tuberculosis H37Rv was done by a recombineering method (20,21). H37Rv/pJV53 was grown to log phase (OD 600 of 0.5) in 7H9 medium containing 25 g/ml of kanamycin before being induced with 0.2% acetamide overnight.…”
Section: Methodsmentioning
confidence: 99%